Impacts of Litter Composition on the Structure and Functional Pathways of Soil Microbial Community during Phyllostachys Edulis Expansion - Huiyun Dong; Shuai Shao; Chenfei Liang; Qiufang Xu; Junhui Chen; Hua Qin (Agronomy, 2022)
Forest ecosystem succession plays an important role in soil microbiota variation, and soil microbes will re-establish ecosystem function after disturbance events. A distinctive disturbance of the expansion of bamboo forest into the surrounding broadleaved ecosystem is the change in litter type input. We conducted a 6-month microcosm experiment to examine the effects of proportional changes in leaf litter composition due to moso bamboo (Phyllostachys edulis) invasion into a broadleaved forest on soil microbial community. A series of mixed litters were prepared with bamboo litter occupying at 0%, 33%, 50%, 67% and 100% in proportion (with a decrease in litter carbon (C)/nitrogen (N) from 36.23 to 31.35), and they were then amended into a broadleaved forest soil at a rate of 1%, respectively. Soil bacterial and fungal communities at different incubation stages were determined by high-throughput sequencing. With the increasing proportion of bamboo litter, the broadleaved forest soil exhibited strong changes in microbiome assembly, including reducing bacteria alpha-diversity, the relative abundance of Acidobacteria and Basidiomycota, while increasing the relative abundance of Actinbacteria, Proteobacteria and Ascomycota. Moreover, the increased proportion of bamboo litter (0% PP→100% PP) increased the relative abundance of membrane transport and carbohydrate metabolism of soil bacteria but decreased the relative abundance of saprotrophic soil fungi. Redundancy analysis showed that bacteria rather than fungal communities changed greatly during incubation (p < 0.05). Additionally, the activities of soil pH, NO3−-N, NH4+-N, dissolved nitrogen and C- and N- acquiring enzymes were the main factors affecting bacterial and fungal community structure (p < 0.05). The soil physicochemical properties were significantly correlated with the composition of microbial phyla among different litter amendment treatments. These results indicated that different proportions of bamboo litter dramatically alter the soil bacterial rather than the fungal community, most likely by changing edaphic patterns. This study has important implications for understanding the litter–soil–microbe synergy during the bamboo forest expansion and provides a basis for assessing the ecological risk of bamboo forest expansion.